Optimasi Faktor Eksposi Pemeriksaan Radiologi Thorax melalui Pengukuran Entrance Surface Dose (ESD) dengan Phantom pada Kondisi Kegawatdaruratan - Astari, Fisnandya Meita; Mahanani, Ayu; Antika, Winona Fajar (Jurnal Ragam Pengabdian, 2026)
Background: Emergency thorax radiography in the ER/ICU using mobile X-rays often faces space constraints and challenging patient positioning, risking higher radiation exposure. Objective: This study aims to determine the Entrance Surface Dose (ESD) values in thorax radiography and identify the optimal combination of exposure factor parameters to minimize ESD. Methods: This quantitative experimental study was conducted at the Radiology Laboratory of Universitas 'Aisyiyah Yogyakarta in February 2026 using an Anthropomorphic Thorax Phantom and a BMX-AR 30 mobile X-ray unit. Variations included FFD (100, 120, 150, 180 cm) and several exposure factors. ESD values were measured using a Raysafe X2 multimeter. Results: Increasing FFD consistently reduced ESD values. While FFD 180 cm yielded the lowest dose, it is impractical in critical care. As a pragmatic middle ground, FFD 120 cm is the most realistic clinical choice. By implementing a high kV-low mAs technique, the combination of 86 kV and 4 mAs at FFD 120 cm proved to be the best parameter, minimizing the ESD value to 0.3 mGy. Conclusion: This study successfully mapped ESD values and identified the optimal exposure combination (86 kV, 4 mAs, FFD 120 cm) to minimize radiation doses safely below the national DRL limit.